Orientalismo contemporáneo: la creación de un nuevo sistema bipolar en las relaciones internacionales - Ettmueller, Eliane Ursula (UNISCI Discussion Papers, 2007)
This article is an aproximation to the new bipolar system in international relations (West – East or Islamic world) that has replaced the two blocks of the Cold War (Capitalism – Communism). It analyzes the new ideology fostered by the Western block in order to justify its global policies. This ideology is just an innovation of a concept with a long tradition, which we will call in its current form “neo-orientalism” or “contemporary orientalism”. The article briefly describes the evolution of orientalism, analyzes the nature of contemporary orientalism and concludes with some remarks on how it could be overcome